Effect of fertility levels on growth and productivity of pearlmillet (Pennisetum glaucum)-based intercropping systems under rainfed condition - Giana, G.K.; Sharma, O.P.; Kuri, B.R.; Shivaran, A.C.; Boori, P.K. (Annals of Agricultural Research, 2016)
A field experiment was conducted during the rainy (kharif) season of 2013 at Jobner, Rajasthan tostudy the effect of fertility levels on growth, yield and equivalent yield of pearlmillet (Pennisetumglaucum)-based intercropping systems under rainfed condition. The treatments consisted of 4intercropping systems viz. sole pearlmillet, pearlmillet + clusterbean, pearlmillet + mungbean andpearlmillet + cowpea with 4 fertility levels viz. no fertilizer, 30 kg N + 15 kg P2O5, 45 kg N + 22.5 kgP2O5 and 60 kg N + 30 kg P2O5/ha. The highest plant heights (182.0 cm) of pearlmillet at harvestingstage were recorded with pearlmillet + clusterbean intercropping system. Sole pearlmillet recordedsignificantly higher effective tillers/plant (2.70), grain (2.04 t/ha) and stover (5.19 t/ha) yields ofpearlmillet over pearlmillet intercropped with mungbean and cowpea. Whereas, pearlmilletequivalent yield (36.0 t/ha) and net returns (`45.2 Ã— 103/ha) was observed significantly highest inpearlmillet + clusterbean intercropping system. Fertility level increasing up to 45 kg N + 22.5 kgP2O5/ha were recorded significantly higher growth parameters, yield attributes, grain and stoveryields as well as pearlmillet equivalent yield and net returns over control and 30 kg N + 15 kg P2O5/ha.